2019
DOI: 10.1093/nar/gkz246
|View full text |Cite
|
Sign up to set email alerts
|

AnnoTree: visualization and exploration of a functionally annotated microbial tree of life

Abstract: Bacterial genomics has revolutionized our understanding of the microbial tree of life; however, mapping and visualizing the distribution of functional traits across bacteria remains a challenge. Here, we introduce AnnoTree—an interactive, functionally annotated bacterial tree of life that integrates taxonomic, phylogenetic and functional annotation data from over 27 000 bacterial and 1500 archaeal genomes. AnnoTree enables visualization of millions of precomputed genome annotations across the bacterial and arc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
278
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(279 citation statements)
references
References 42 publications
1
278
0
Order By: Relevance
“…Many contigs from these libraries are phage-associated (30%; table S4, 141 figure 2A) and many encode genes of unknown function (figure S4); these are both hallmarks of known 142 acrs (Borges et al, 2017;Pawluk et al, 2017;Sontheimer and Davidson, 2017). Additionally, we 143 observed that Cas9 homologs are found in 15 of the 18 bacterial genera identified in these selections 144 (83%, table S4), a significant enrichment over the 12% of bacterial genera that harbor Cas9 (567/4822) 145 from a representative set of ~24,000 bacterial genomes (Mendler et al, 2018) (p=4x10 -21 , χ² test). This 146 enrichment strongly supports our hypothesis that many of the recovered contigs encode true acrs rather 147 than artifacts of functional selection, since phages and MGEs must encounter Cas9 to benefit from the 148 protective effect of acrs.…”
Section: Introduction 14mentioning
confidence: 70%
“…Many contigs from these libraries are phage-associated (30%; table S4, 141 figure 2A) and many encode genes of unknown function (figure S4); these are both hallmarks of known 142 acrs (Borges et al, 2017;Pawluk et al, 2017;Sontheimer and Davidson, 2017). Additionally, we 143 observed that Cas9 homologs are found in 15 of the 18 bacterial genera identified in these selections 144 (83%, table S4), a significant enrichment over the 12% of bacterial genera that harbor Cas9 (567/4822) 145 from a representative set of ~24,000 bacterial genomes (Mendler et al, 2018) (p=4x10 -21 , χ² test). This 146 enrichment strongly supports our hypothesis that many of the recovered contigs encode true acrs rather 147 than artifacts of functional selection, since phages and MGEs must encounter Cas9 to benefit from the 148 protective effect of acrs.…”
Section: Introduction 14mentioning
confidence: 70%
“…The observation that distributions of traits are variable, sometimes patchy, and potentially decoupled from phylogenetic relatedness raises the possibility that more complex, enzyme-specific patterns might underlie processes contributing to metabolic diversity in the CPR. To address this, we drew upon trait distributions to compute two metrics -one to quantify the average branch length of clades in which a trait is conserved (phylogenetic depth) and a second, patchiness, related to the number of gains/losses of a binary trait over a tree (see Materials and Methods) (Mendler et al, 2019) . These metrics were then integrated to create an 'evolutionary profile' for each trait.…”
Section: Functionally Linked Metabolic Genes Display Different 'Evolumentioning
confidence: 99%
“…The list of transformable species keeps growing, now including species that had long been considered incapable of transformation 12 . In addition, from the recent database AnnoTree grouping nearly 24,000 bacterial genomes 13 , we uncover that transformation-specific genes required for the uptake of eDNA (comEC, dprA) are extremely conserved (Fig. 1).…”
Section: Introductionmentioning
confidence: 92%